The Interpretation of the Role of a Polyketide Synthase ClPKS18 in the Pathogenicity of Curvularia lunata - Lu, Zhixiang; Wang, Shaoqing; Dou, Kai; Ren, Jianhong; Chen, Jie (Frontiers in Microbiology, 2022)
Plant pathogenic fungus Curvularia lunata (Wakker) Boedijn causes leaf spot diseases in several plants such as, Oryzae sativa, Sorghum bicolor (L.) Moench and Capsicum frutescens. It has been spread worldwide, specifically maize growing regions. The polyketide synthetase (PKS) plays a significant role in secondary metabolite production and its effect on the virulence. The Clpks18 of C. lunata, strongly correlated with its pathogenicity. The role of Clpks18 on pathogenic activity of C. lunata remain unclear. Hence in the present study, the importance of Clpks18 on the hyphae and conidial melanization and its on the sporulation and hyphal growth. The deletion of Clpks18 reduced the production of Methyl 5-(hydroxymethyl) furan-2-carboxylate toxin. The virulence of ΔClpks18 mutant was significantly reduced compared to the wild type. The metabolomics data revealed that (R)-(-)-Mellein was as a vital factor for the virulence of C. lunata. The (R)-(-)-Mellein and toxin produced by C. lunata were detected in the maize leaves during its infestation. in addition, metabolomic analysis showed that the Clpks18 influence the Glycerolipid, non-ribosomal peptide biosynthesis and its metabolism. This study demonstrates that the Clpks18 gene is important for the pathogenicity of C. lunata by influencing the complex metabolic network